Correlações entre o estresse e as habilidades sociais em crianças com deficiência intelectual - Lima, Celiany Alves Garcia (2019)
Introduction: The set of social skills refers to the existence of different classes of social behaviors presented by the individual to deal with their interpersonal situations. Injury to these skills can lead to depression, anxiety, stress, and disruptive behaviors. Stress is understood as a reaction of the body that causes psychophysiological changes in the child. Children with intellectual disabilities have deficits in social skills and fewer resources to cope with stress. The correlation of these variables, stress and social abilities, under the child's own perception, seeks new discussions to think of practical strategies that affect beyond the child, the family and the school in order to effect the inclusion of these children in society. The objective of this study was to evaluate the existence of a correlation of stress and social skills in children with intellectual disability, from the perspective of the child. Methods: 31 children with their respective parents diagnosed with intellectual disability participated in the study, accompanied at a specialized rehabilitation center in southeast Minas Gerais, Brazil. The Brazilian Economic Classification Criteria, the Child Stress Scale (ESI) and the Social Skills Assessment System (SSRS-BR) were used as instruments of data collection. The data of the scales were analyzed according to the standardization of the authors of the instruments. The ESI was only validated for children without disabilities, so the t-test was used to compare the mean of the scale and that found in this study. The analysis was done in the Statistical Package for the Social Sciences program and the Pearson correlation coefficient was used to associate the variables of interest. A significance level of 5% was considered. Results: A total of 64.5% of the children had a stress picture; the psychological reactions with depressive components were the most frequent with 64.5% of the answers; 70.0% of the children had deficits in social skills; the psychological reactions with depressive components presented a low and significant negative correlation with the social skills scale (r = 0.26; p = -0.400); children and parents presented significant correlations among the factors of the social skills scale, presenting the same perceptions about children's repertoire of abilities. Conclusion: important contributions were found in assessing the correlation between stress and social skills, and also in analyzing the perception of children with intellectual disabilities, who, for various factors, are not accustomed to talking about their own feelings. The results found have the potential to trigger new discussions and to stimulate the creation of new public policies on health and education.